Jiwa dan Qalbu dalam Hadis - Adnir, Farid; Ginting, Ernawati Beru (UIN Sumatera Utara Medan, 2023)
Discussion among tasawwuf experts about spirit, qalb, reason and lust. There are those who equate and there are also those who differentiate them. In Ulumuddin's ihya, Al-Gazali discusses the spiritual structure of humans with elements, first, the qalb. Qalb has two meanings, namely physical and metaphysical. Spirit refers to a living thing. Because in fact it is the spirit that animates creatures. The spirit is also said to be inanimate objects. For example, this book has a spirit, in that case what is meant by the expression of the spirit is the parable that the object is valuable. It doesn't mean that the book has a life, on the contrary the book has a value that animates, or moves. The heart is a drive shaft for every component in the body system and supports its performance system. The heart lies in the middle, guarded and protected by the body. The heart is the noblest component of the body, the main source of life for the animal spirit and natural instincts. The heart can be said to be the main core of reason, knowledge, gentleness, and courage, nobility, patience, fortitude, love, desire, willingness, anger, and all the qualities of perfection. Every member both from outside and inside and its use as a servant from the heart